Asymmetric desymmetrization of meso-diols by C2-symmetric chiral 4-pyrrolidinopyridines - Schedel, Hartmut; Kan, Keizo; Ueda, Yoshihiro; Mishiro, Kenji; Yoshida, Keisuke; Furuta, Takumi; Kawabata, Takeo (Beilstein Journal of Organic Chemistry, 2012)
In this work we developed C2-symmetric chiral nucleophilic catalysts which possess a pyrrolidinopyridine framework as a catalytic site. Some of these organocatalysts effectively promoted asymmetric desymmetrization of meso-diols via enantioselective acylation.
Keywords: acylation; desymmetrization; hydrogen bond; meso-diol; nucleophilic catalyst; organocatalysis